Eletrodeposição de níquel e ligas níquel-ferro em solventes eutéticos baseados em cloreto de colina - Urcezino, Amanda da Silva Cardoso (2017)
The aim of this work was the study of electroplating of Ni and Ni-Fe alloys onto Cu, using two deep eutectic solvents based on choline chloride (ChCl), composed by ChCl and ethylene glycol (EG) or urea (U), in the 1ChCl:2 (EG or U) molar ratio, replacing the water. Thus, they were used the techniques of UV-Vis absorption spectroscopy (UV-Vis), cyclic voltammetry (CV), chronoamperometry, scanning electron microscopy (SEM) coupled to the dispersive X-ray spectroscopy (EDX), linear polarization and Raman spectroscopy. The UV-Vis spectra showed that both the nickel as iron formed complexes with ligands EG or U. CV studies evidenced that ChCl:2U exhibited greater sensitivity to moisture than ChCl:2EG. The temperature increase from 25 °C to 70 °C favored the electrochemical processes kinetics by increasing the current values, both in the absence such as in the presence of metals, as well as shifted the reduction potentials, from −1.25 V to −0.91 V in ChCl:2U and from −1.07 V to −0.92 V in ChCl:2EG. The voltammograms obtained in the presence of nickel showed the existence of a cathodic process associated with its reduction and a nucleation loop, whose overpotential diminished with increasing temperature, from 0.32 V to 0.21 V in ChCl:2U and from 0.38 V to 0.36 V in ChCl:2EG. The voltammograms obtained in the presence of nickel and iron in ChCl:2U showed two processes, one (−0.90 V) associated with the reduction of nickel and the other, to the iron (−1.12 V). In ChCl:2EG, a third process was defined with increased iron concentration, suggesting that the reduction of this metal occurs in more of a step. The diffusion coefficients of nickel ranged from 2.2 × 10−9 cm2 s−1 (25° C) to 3.7 × 10−8 cm2 s−1 (70° C) in ChCl:2U and 1.3 × 10−8 cm2 s−1 (25° C) to 5.8 × 10−8 cm2 s−1 (70° C) in ChCl:2EG. The nucleation and growth process of nickel on copper was determined as progressive in ChCl:2U and instantaneous in ChCl:2EG by applying the model of Scharifker and Hills. The results of SEM and EDX showed that there was film deposition of Ni and Ni-Fe in both solvents and that films obtained using ChCl:2U were homogeneous, while those obtained in using ChCl: 2EG presented cracks. The increase of current density led to the decrease in deposition efficiency (from 96 % to 61 %, for example). Polarization curves showed that the increase in the amount of iron in coatings from 0 to 43.3 % caused a decrease in resistance to polarization, whose values ranged from 3.0 to 13.8 kΩ cm2.